FAKTOR INTERNAL DAN KINERJA PERBANKAN - Fajar Sukma Dipura; Deny Dwi Hartomo (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2016)
This study aimed to determine the effect of capital adequacy, liquidity, credit risk, net income interest, and GWM on the performance of banks with a proxy variable return on asset in the banks listed on the Indonesia Stock Exchange in the observation for the yearperiod 2011-2015.CAR, LDR, NPL, NIM, and GWM are variables that is obtained from the the financial statements or the calculation of annual report banking ended on December 31, were taken from the Otoritas Jasa Keuangan in years 2011-2015. Population used in this research is all banks in Indonesia. Used purposive sampling method, have been selected 27 samples of banks listed on the BEI and has a complete financial report on the years 2011-2015. The analytical method used is multiple linear regression analysis.The results of this research concluded: Simultaneously this model affect the ROA’s banks, but partially, (1) CAR has a significant negative impact on ROA’s banks, (2) LDR has a significant negative impact on the ROA’s banks, (3) NPL has a significant negative impact on ROA’s banks, (4) NIM has a positive significant effect on ROA’s banks (5) GWM has significant negative effect on ROA’s banks.